Atypical Lung Parenchymal Bronchogenic Cyst Complicated by Tuberculosis Infection - Haiqing Chu; Xianghua Yi; Lan Zhao; Tao Gui; Xia Fang; Xiwen Sun (Canadian Respiratory Journal)
A bronchogenic cyst (BC) is a rare congenital lesion that may cause life-threatening organ compression in children, but is generally asymptomatic in adults unless there are other complications. In the present report, a 34-year-old woman in whom a BC was complicated by tuberculosis infection is described. Due to the small size of the BC, it was asymptomatic and could not be diagnosed until she was treated with antituberculosis medications.